Materials for Construction and Civil Engineering : Science, Processing, and Design - Gonçalves, M. Clara; Margarido, Fernanda (Springer International Publishing : Imprint: Springer, 2015)
This expansive volume presents the essential topics related to construction materials composition and their practical application in structures and civil installations. The book's diverse slate of expert authors assemble invaluable case examples and performance data on the most important groups of materials used in construction, highlighting aspects such as nomenclature, the properties, the manufacturing processes, the selection criteria, the products/applications, the life cycle and recyclability, and the normalization. Civil Engineering Materials: Science, Processing, and Design is ideal for practicing architects; civil, construction, and structural engineers, and serves as a comprehensive reference for students of these disciplines. This book also: ·       Provides a substantial and detailed overview of traditional materials used in structures and civil infrastructure ·       Discusses properties of natural and synthetic materials in construction and materials' manufacturing processes ·       Addresses topics important to professionals working with structural materials, such as corrosion, nanomaterials, materials life cycle, not often covered outside of journal literature ·       Diverse author team presents expect perspective from civil engineering, construction, and architecture ·       Features a detailed glossary of terms and over 400 illustrations  .